PENINGKATAN HASIL BELAJAR PERHITUNGAN YANG BERKAITAN DENGAN UANG MENGGUNAKAN MEDIA UANG MAINAN PADA SISWA KELAS IV UPTD SD INPRES OETETE 2 KOTA KUPANG - Yasintha Kikhau; Wara Sabon Dominikus; Vera Rosalina Bulu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve the learning outcomes of money calculation in fourth-grade students at UPTD SD Inpres Oetete 2 Kupang City through the use of toy money media. The study is motivated by the low learning outcomes of students on money calculation material due to conventional learning methods that lack active student participation. The study uses the Classroom Action Research (CAR) method with two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation sheets and tests, then analyzed descriptively. The results of the observation study show a significant increase: the average student score increased from 46.9 (pre-cycle) to 66.9 (Cycle I) and 89.2 (Cycle II). The percentage of learning completeness also increased from 19.2% (pre-cycle) to 53.8% (Cycle I) and 92.3% (Cycle II). These findings indicate that the toy money media is effective in increasing student engagement and learning outcomes through interactive and enjoyable learning. This approach not only improves mathematical understanding but also develops critical thinking and collaboration skills. The study concludes that toy money media can be an effective strategy to overcome the challenges of mathematics learning at the elementary school level.